Effect of Non-Structural Components on the Dynamic Response of Steel-Framed Floors: Tests Before and After Component Installations - Royvaran, Mohammad; Avci, Onur; Davis, Brad (Frontiers in Built Environment, 2021)
The effect of partition walls and non-structural elements on the dynamic response of floors is still not well understood, and there is a need for vibration testing of floors at various stages of construction. The best way to shed some light on the effect of non-structural components is to test additional floors (preferably the same floor) before and after the installation of non-structural elements and compare the dynamic properties. For that purpose, the authors conducted vibration testing on a building floor under construction at various stages of fit-out to quantify the effects of various non-structural elements on the vibration response. An elevated floor of a steel-framed building in the Southeastern United States was tested: the first test was performed for the bare slab conditions with minimal non-structural elements, while the second test was conducted after the installation of non-structural components and in the presence of various construction materials spread over the test floor. The modal tests were conducted by applying measured dynamic forces using an electrodynamic shaker while accelerations were measured at critical locations on the slab. The measurements were post-processed to determine the frequency response functions, which provided general information on the dynamic response. The selection of the test points and excitation functions were primarily to extract maximum data regarding the performance of non-structural elements rather than as part of a standard vibration serviceability assessment of the floor structure. The modal tests were repeated after the installation of non-structural components, electrical and mechanical ductwork to determine their effect on the vibration characteristics of the floor. The resulting frequency response functions were compared for each condition, and finite element models were created to represent each test condition. As a result, the installation of non-structural components was observed to influence the dynamic response of the floor. Combined with the other test data in the literature, the results of the experimental testing presented in this paper might lead to more effective modeling techniques and provide guidance as to their inclusion into analytical models.